Pengaruh Laba, Capital Intensity, Leverage, dan Aktivitas Terhadap Financial Distress Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Delia Nur Syafella; Ramadona Simbolon; Lusi Elviani Rangkuti (Universitas Islam Islam Sumatera Utara, 2022)
This study aims to examine the effect of profit, capital intensity, leverage and activity on financial distress. The research sample was selected using a purposive sampling method, namely 51 manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020 and published complete financial statements in Rupiah. The analytical method used in this research is quantitative analysis with multiple linear regression. The results of this study indicate that the variables Capital intensity, Levareg, and Activity have a positive and significant effect on financial distress. While the profit variable has a negative and significant effect on financial distress. Taken together, the variables of Profit, Capital intensity, Leverage, and Activity together have a significant effect on Financial distress